An evaluation of the Rape Crisis Cape Town Trust's Birds and Bees peer education programme in Khayalitsha - Strydom, Sarah Jean (Institute for Monitoring and Evaluation, 2015)
This dissertation reports a theory, process and outcome evaluation of the Rape Crisis Cape Town Trust's (RCCTT) Birds and Bees programme. The Birds and Bees is a peer education programme that aims to create safer schools by decreasing incidents of sexual violence in schools and increasing the reporting of sexual violence. The programme in its current form has been implemented in high schools in Khayelitsha since 2009 and this dissertation focuses on two high schools in Khayelitsha that received the programme throughout 2013.The Birds and Bees programme theory was investigated for its utility and plausibility and a revised programme theory was proposed. Eight questions relating to the implementation of the programme were posed in order to assess whether the programme was implemented as intended. These questions related to the selection and attendance of peer educators, their ability to fulfil their role, the suitability of the peer educators' supervisors and the implementation of school activities and supervision meetings. Five questions regarding outcomes were posed that enquired about the effectiveness of the school safety plan, the number of learners who approached the peer educators for advice and the number of learners who reported sexual violence and accessed the services of the RCCTT. The evaluation used secondary data collected throughout 2013 and included interviews with the programme coordinator and the two supervisors responsible for the training and supervision of the peer educators. Data analysis methods included the use of descriptive statistics for the pre- and post-test data and QSR International's NVivo 10 software for qualitative data.